Snowmass2021: letter of interest cosmology intertwined IV : the age of the universe and its curvature - Valentino, Eleonora di; Anchordoqui, Luis A.; Akarsu, Özgür; Ali-Haimoud, Yacine; Amendola, Luca; Arendse, Nikki; Asgari, Marika; Ballardini, Mario; Basilakos, Spyros; Battistelli, Elia; Benetti, Micol; Birrer, Simon; et al. (Astroparticle physics, 2021)
A precise measurement of the curvature of the Universe is of prime importance for cosmology since it could not only confirm the paradigm of primordial inflation but also help in discriminating between different early-Universe scenarios. Recent observations, while broadly consistent with a spatially flat standard Λ Cold Dark Matter (ΛCDM) model, show tensions that still allow (and, in some cases, even suggest) a few percent deviations from a flat universe. In particular, the Planck Cosmic Microwave Background power spectra, assuming the nominal likelihood, prefer a closed universe at more than 99% confidence level. While new physics could be at play, this anomaly may be the result of an unresolved systematic error or just a statistical fluctuation. However, since positive curvature allows a larger age of the Universe, an accurate determination of the age of the oldest objects provides a smoking gun in confirming or falsifying the current flat ΛCDM model.